Experimental and simulation studies on FTO/ZnO:Co/CuO hetero-junction structure for solar cell application. (13th September 2019) - Dabbabi, Samar; Garcia-Loureiro, A; Ajili, Mejda; Ben Nasr, Tarek; Kamoun, Najoua
Abstract: The performance of FTO/ZnO:Co/CuO hetero-junction structure is investigated using the Slivaco-Atlas software. The single oxide films were prepared by spray pyrolysis method on glass substrates in order to characterize the proper material parameters. Structural and morphological analysis confirmed the deposition of FTO, ZnO:Co, and CuO films with porous structures. The extracted physical properties such as thickness, optical and electrical parameters are considered as input data for Silvaco-Atlas software simulation. It was found that thickness layers and carrier concentration of CuO based solar cell play an important role in determining solar cell performances. The combination of the optimum parameters enables to obtain the efficiency of 24.55% which is improved with 8.88% compared to the calculated one using the proper experimental parameters.